The Effect of Soft Skills on the Successful Employment of Future Engineers: Self-Evaluation Results - L. V. Bondareva; T. V. Potemkina; G. S. Saulembekova (Moscow Polytechnic University, 2022)
The research focuses on "integrating" technological universities' graduates in the current labor market. In pedagogical practice, it is widely known that university graduates with welldeveloped "soft" skills feel more confident about their future, and they can more easily cope with job search. In order to identify the effect of "soft" skills on the readiness of future engineers to job search, a survey was conducted among 106 students, including programmers, business analysts, IT designers, materials scientists, and nanotechnologists.The authors used the statistical methods to identify the relationship between students' self-evaluation of "soft" skills and their readiness for job-seeking. We have found that 71.7% of all respondents who determined a high level of proficiency in "soft" skills, only 29.6% are confident that job search should not cause difficulties, 28.8% can see a clear connection between their studies and future profession, and 37% believe that they have motivation for professional fulfillment.The results of the survey based on self-evaluation showed that in spite of having a high score in evaluating their "soft" skills, the respondents express extreme uncertainty that they will be competitive enough outside the university and that will be prepared to apply the skills which are crucial for successful employment.